2020
DOI: 10.1101/2020.12.24.423824
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CLN5 and CLN3 function as a complex to regulate endolysosome function

Abstract: CLN5 is a soluble endolysosomal protein that regulates the itinerary of the lysosomal sorting receptor sortilin. Mutations in this protein cause neuronal ceroid lipofuscinosis, a rare neurodegenerative disorder, and have also been associated with Alzheimer’s disease, suggesting functional defects in a common pathway. We previously found that depletion of CLN5 leads to dysfunctional retromer, resulting in the degradation of the lysosomal sorting receptor, sortilin. However, how a soluble lysosomal protein can m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Although we did not find a change in lysosomal area and intensity with CLN5 inhibition in our iPSC-derived CLN5-deficient human neurons, we did detect an increased number of non-motile lysosomes (Figure 2I) in CLN5-deficient neurons with the overall number of lysosomes remaining the same (Figure 2E). The increased number of non-motile lysosomes explains the accumulation of lysosomes, seen in the CLN5-deficient neurons (Figure 2A, 2 nd , 3 rd and 4 th panels), and as reported by Uusi-Rauva et al Another study of CLN5 in HeLa cells by Yasa et al (2021) [19] suggested that CLN5 KO HeLa cells were not able to move lysosomes as efficiently as wild type HeLa cells. In our study, impaired anterograde movement in the CLN5-deficient human neurons could indicate that the neuronal projections are being exempt from getting their waste cleared, which could cause neuronal toxicity at the synapses.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Although we did not find a change in lysosomal area and intensity with CLN5 inhibition in our iPSC-derived CLN5-deficient human neurons, we did detect an increased number of non-motile lysosomes (Figure 2I) in CLN5-deficient neurons with the overall number of lysosomes remaining the same (Figure 2E). The increased number of non-motile lysosomes explains the accumulation of lysosomes, seen in the CLN5-deficient neurons (Figure 2A, 2 nd , 3 rd and 4 th panels), and as reported by Uusi-Rauva et al Another study of CLN5 in HeLa cells by Yasa et al (2021) [19] suggested that CLN5 KO HeLa cells were not able to move lysosomes as efficiently as wild type HeLa cells. In our study, impaired anterograde movement in the CLN5-deficient human neurons could indicate that the neuronal projections are being exempt from getting their waste cleared, which could cause neuronal toxicity at the synapses.…”
Section: Discussionsupporting
confidence: 82%
“…Another study of CLN5 in HeLa cells by Yasa et al . (2021)[19] suggested that CLN5 KO HeLa cells were not able to move lysosomes as efficiently as wild type HeLa cells. In our study, impaired anterograde movement in the CLN5-deficient human neurons could indicate that the neuronal projections are being exempt from getting their waste cleared, which could cause neuronal toxicity at the synapses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCL pathologies are linked to the dysfunction of several CLN proteins involved in intracellular trafficking (13,39). To assess if the delay in SG dissolution is CLN3 specific, we investigated SG dynamics in a HeLa KO model of CLN5 disease.…”
Section: Resultsmentioning
confidence: 99%
“…The precursor Cln5 protein is a 407-amino acid-long membranelocated protein that is cleaved by signal peptide peptidase (SPP) and its homologs the SPP-like proteases (SPPL), resulting in the soluble Cln5 protein (7). Several studies have demonstrated Cln5 localized to lysosomes (8,9) and associated with endolysosomal dysfunction (10)(11)(12). However, the structure and molecular function of the Cln5 protein remains unknown (13), precluding a mechanistic understanding and potential treatment development for Cln5dependent NCL.…”
Section: Introductionmentioning
confidence: 99%